METODE PENENTUAN VOLUME AGGREGAT PONDASI JALAN BERDASARKAN VARIASI DAN KESALAHAN: STUDI KASUS - Marsinta Simamora; Jati Utomo Dwi Hatmoko (TEKNIK, 2013)
Variations between plans and reality can hardly be avoided in construction projects. These variations may beaccepted when they are still in the acceptance limits, or rejected when they are beyond the acceptance limits.The former is called variation in acceptance and the later is called error. Distinguishing these two in acompleted construction work is very important, as rejected variations (errors) may be considered as breaching acontract, thus may have legal implications. The research aims to evaluate the traditional calculation method(MeTrad) and to promote variation acceptance and error approach (MeVE) that is able to draw a clear linewhether a particular work to be accepted and rejected. The research was conducted by comparing the results ofcalculation of the aggregate volume between MeTrad and MeVE. The data was collected from Mauponggo-Puuwada road project in Nangakeo in 2010. The results show that there was no difference in the volumescalculated using both methods. The volume of Class B aggregate based on MeTrad calculation is 386.01m 3andthe volume based on MeVE is 386.01m3; where 16.67m3 of which (3.34% of the planned volume) is in the rangeof acceptance and 369.34m3 of which (73.94% of the planned volume)is the volume that is rejected (error). Theresults suggest that MeTrad cannot distinguish clearly whether the work is within the limits of acceptance orrejection, while on the other hand MeVE can describe in detail parts of the work to be accepted or rejected.Using this MeVE calculation, an assessment of a construction workis expected to be more objective anddetailed.